Transforming global information and communication markets the political economy of innovation - Cowhey, Peter F., 1948- (MIT Press, 2009)
Innovation in information and communication technology (ICT) fuels the growth of the global economy. This examination of ICT from a political economy perspective argues that innovation and economic growth require new approaches in global governance that will reconcile diverse interests and enable competition to flourish.
Keywords: Technological innovations -- Economic aspects.; Information technology -- Technological innovations.; Information technology -- Economic aspects.; Telecommunication -- Technological innovations.; elektronické knihy; electronic books